2013
DOI: 10.1038/clpt.2013.115
|View full text |Cite
|
Sign up to set email alerts
|

Defining “Innovativeness” in Drug Development: A Systematic Review

Abstract: Some observers of drug development argue that the pace of pharmaceutical innovation is declining, but others deny that contention. This controversy may be due to different methods of defining and assessing innovation. We conducted a systematic review of the literature to develop a taxonomy of methods for measuring innovation in drug development. The 42 studies fell into four main categories: counts of new drugs approved, assessments of therapeutic value, economic outcomes, and patents issued. The definition de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 58 publications
(83 reference statements)
1
49
0
5
Order By: Relevance
“…4 Drug innovation can be defined in many ways. 5 For the purposes of our study, a transformative drug was defined as one that both was innovative and had a groundbreaking effect on patient care. In two cases, a drug class as a whole was identified as being transformative in the study period, even though the first member of the class was approved by the Food and Drug Administration (FDA) before the beginning of the period (for an explanation of the methods used in selecting the study drugs, see the online Appendix).…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…4 Drug innovation can be defined in many ways. 5 For the purposes of our study, a transformative drug was defined as one that both was innovative and had a groundbreaking effect on patient care. In two cases, a drug class as a whole was identified as being transformative in the study period, even though the first member of the class was approved by the Food and Drug Administration (FDA) before the beginning of the period (for an explanation of the methods used in selecting the study drugs, see the online Appendix).…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Systematically quantifying differences in quality between drugs tends to be difficult; as Kesselheim, Wang, and Avorn (2013) write, prior work has looked at a variety of measures including the number of citations a drug receives in the medical literature, the number of citations its main patent receives, or simply its sales. My approach is to follow Lanthier et al (2013) and Dranove, Garthwaite, and Hermosilla (2014) in asking whether a drug received a priority review designation from the FDA.…”
Section: Imitation or Innovation?mentioning
confidence: 99%
“…However, studies published in the last decade that measured the therapeutic value reported a negative trend in the innovation of new drugs. A reduced number of drugs with important innovations was detected in all studies included in the systematic review, regardless of the method used for measuring the therapeutic value 48 . This study analyzes innovation in the perspective of the therapeutic value measurement.…”
Section: Discussionmentioning
confidence: 99%
“…This controversy arises because different methods of defining pharmaceutical innovation are used 1,6,7,48 . A systematic review with the objective of identifying the methods used in determining pharmaceutical innovation trends developed a taxonomy of the strategies employed in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation